Dynamic response of double skin façades under blast loads. (15th September 2016) - Ding, Chao; Ngo, Tuan; Mendis, Priyan; Lumantarna, Raymond; Zobec, Marc
Highlights: Blast simulation in LS-DYNA was validated through test results and SDOF approach. Coupled 2DOF approach integrates theories of 2DOF analysis with adiabatic process. Coupled 2DOF approach is used to model the dynamic response of DSF under blast load. UFC is insufficient to address the dynamic response of DSF under blast load. Abstract: Blast loads pose devastating threats on façade systems. Fragments from glass façades can cause injuries or even fatalities. Double skin façades (DSF) are becoming increasingly popular in modern façade construction practices due to their energy efficiency. In addition, DSF exhibit a higher blast resistance capacity compared to single layer (monolithic) façades. The Unified Facilities Criteria (UFC) 3-340-02 (2008) provides approaches to assess blast performance of monolithic glass panels. However, due to the complex interactions between DSF panels and the air within the cavity, current codes are insufficient to address the blast responses of DSF. This paper presents analytical approaches to obtain maximum deformations (centre) of the DSF panels subjected to blast pressures. A blast trial was described in this paper for validating the blast pressure simulation in LS-DYNA. The dynamic response of the monolithic panes simulated by LS-DYNA was then validated against the single degree of freedom (SDOF) approach. The key theoretical backgrounds of the analytical model are the two degree of freedom (2DOF) approach and adiabatic process. Based on those two theories, a coupled 2DOF analysis was then proposed, since it combined the analysis of the two panes and the air cavity between them. Blast responses of DSF in the elastic regime using the coupled 2DOF approach conformed well to the validated LS-DYNA simulation results. By comparing the results from the coupled 2DOF approach and UFC 3-340-02, it was found that UFC is over-conservative. Therefore, in terms of engineering applications, the analytical model provides an efficient and accurate approach to assess the blast responses of DSF in the linear-elastic regime.